Vaccination controllers for SEIR epidemic models based on fractional order dynamics. (September 2017) - NasimUllah,; Ibeas, Asier; Shafi, M.; Ishfaq, M.; Ali, Mumtaz
Highlights: Novel fractional order robust vaccination controller based on the fractional order SEIR epidemic model. The control law is feasible for practical implementation. Chattering phenomena us minimized using fractional order dynamics. Abstract: This article proposes a novel fractional order robust vaccination controller based on the fractional order SEIR epidemic model which is subject to the parametric uncertainties. Classical sliding mode controller is robust but due to the high frequency chattering phenomena, it is not feasible for practical implementation. To reduce the chattering phenomena, a new fractional order sliding manifold is proposed and a low gain fractional order robust vaccination control law is formulated with same robustness as classical sliding mode control. Effectiveness of the proposed vaccination control strategy is shown through numerical simulations.